Universal series by trigonometric system in weighted Lμ1 spaces - S. A. Episkoposian (International Journal of Mathematics and Mathematical Sciences)
We consider the question of existence of trigonometric series universal in weighted Lμ1[0, 2π] spaces with respect to rearrangements and in usual sense.